MORPHOLOGIC ASSESSMENT OF THE EFFECTIVENESS OF OSTEOTROPIC PREPARATIONS ON BONE TISSUE REGENERATION IN EXPERIMENTAL ANIMALS - Dienha, O.V.; Tsevukh, L.B.; Mirchuk, B.M.; Konovalov, M.F.; Novikova, Zh.O.; Tarasenko, I.Y.; Yudina, O.O. (World of Medicine and Biology, 2024)
The research was devoted to the study of the processes of regeneration of the alveolar process of the jaws of experimental animals under the influence of osteotropic drugs. The study was conducted on 50 Wistar rats of herd breeding aged 30 days at the beginning of the experiment. The duration of the experiment was 30 days. The animals were withdrawn from the experiment under thiopental anesthesia, and the jaws were isolated. Excised fragments of jaw bone tissue were fixed in neutral 10 % formalin, decalcified, and embedded in paraffin. The sections were stained with hematoxylin and eosin. The experimental study on animals made it possible to study the effectiveness of the phased application of osteotropic drugs on the processes of local bone resorption. These studies should be taken into account in the development of treatment and prevention complexes for children with osteogenesis disorders.
Keywords: rats; experimental research; osteogenesis; complex of preparations; carcinogenic diet